Design of 1-Storey Residential Houses with an Eco-Friendly Concept in North Jakarta - Ulinata, Ulinata (Journal Research of Social Science, Economics, and Management, 2025)
Housing is one of the basic human needs. Houses are also a place for humans to take refuge from heat and rain. North Jakarta is one of the administrative cities in DKI Jakarta Province where most of the area is residential areas because the number of people is always increasing from year to year. Therefore, good design is needed from the architectural side so that the houses that are designed and built will provide comfort for their residents. The method used in the research entitled 1-storey Residential House Design with an Environmentally Friendly Concept in North Jakarta is to use a descriptive qualitative method by determining the location, looking for literature studies from articles or books, conducting an analysis at the location, then making drawings of the design of a 1-storey residential house with an environmentally friendly concept. The design drawings are expected to provide comfort for its occupants when they have been built and inhabited.